Pneumectomy and lobectomy in chronic lung abscess, based on 14 operated cases - Sierra, Ramón; Victorica, Alejandro; Suárez, Hamlet; Pifaretti, N (Cirugía del Uruguay, 2020)
Presented at session 23th July 1947